Pembuatan Video Belajar Membaca Bagi Siswa Taman Kanak-Kanak Melalui Youtube Sebagai Media Belajar Yang Menarik di Era Digital - Dina Dahliana; Rahmia Tulljanah; Suang Kupon Syukur (Yayasan Literasi Sains Indonesia, 2022)
The development of a very sophisticated era requires adjustments also with the teaching system. Children today can no longer equate their way of learning with children of old. The digital era is a period where technological developments occur all over the world. As a society that lives in this digital era, we should follow the current technological developments that we feel. technology to solve problems in the world of education is a wise action. Attractive strategies and media will also be the main attraction for children to learn. Therefore, the use of YouTube is one of the media for learning to read for children at this time. With the use of youtube children can learn to read when and play. Along with the development of education, the media currently used by teachers varies greatly. Today, there are many studies that develop learning media, one of which is video media. Video is a type of audio-visual media, meaning learning media that can be seen using the sense of sight and heard using the sense of hearing. As a learning medium, video is effectively used for the learning process en masse, individually or in groups. The survey results show that 69% (very interested) and 31% (interested) if the author makes another video learning to read. This means that the use of learning to read videos as learning media via YouTube is effectively used by children, especially kindergarten age.